Retinal capillary nonperfusion in preclinical diabetic retinopathy - Santos, Torcato (2023)
The aim of the study was to identify retinal microvascular changes using optical coherence tomography angiography (OCTA) in type 2 diabetes (T2D) patients with preclinical retinopathy identified by ultra-widefield fundus photography (UWF-FP). This is a cross-sectional observational study. All patients underwent UWF-FP 200° examinations with OPTOS California (Optos, Dunfermline, UK) and Cirrus AngioPlex® spectral-domain (SD)-OCTA 3 × 3 mm acquisitions (ZEISS, Dublin, CA, USA). The absence of visible lesions was identified using UWF-FP. One hundred and ninety three eyes of individuals with T2D with no visible lesions in the fundus and identified in a screening setting were included in the study. Skeletonized vessel density (SVD), perfusion density (PD), and areas of capillary nonperfusion (CNP) values on SD-OCTA were significantly decreased when compared with healthy population (p < 0.001). SVD and CNP values of the superficial capillary plexus (SCP) were more frequently decreased (35% and 45%, respectively) than SVD values of the deep capillary plexus (DCP) (9% and 15%, respectively), demonstrating that diabetic microvascular changes occur earlier in the SCP than in the DCP. The ischemic phenotype, identified by a definite decrease in SVD or CNP in the SCP may, therefore, be identified in the preclinical stage of diabetic retinal disease. Retinal capillary nonperfusion detected by OCTA metrics of SVD and CNP can be identified in the central retina in eyes with T2D before development of visible lesions in the retina. Our findings confirm the relevance of OCTA to identify macular microvascular changes in the initial stages of diabetic retinopathy, allowing the identification of its ischemic phenotype very early in the disease process.